Cholecystokinin—From Local Gut Hormone to Ubiquitous Messenger - Rehfeld, Jens F. (Frontiers in Endocrinology, 2017)
Abstract Cholecystokinin (CCK) was discovered 1928 in jejunal extracts as a gallbladder contraction factor. It was later shown to be member of a peptide family which are all ligands for the CCK1 and CCK2 receptors. CCK peptides are known to be synthetized in small intestinal endocrine I-cells and cerebral neurons. But in addition, CCK is expressed in several endocrine glands (pituitary cells, thyroid C-cells, pancreatic islets, the adrenals, the testes); in peripheral nerves; in cortical and medullary kidney cells; in cardial myocytes; and in cells of the immune system. CCK peptides stimulate pancreatic enzyme secretion and growth, gallbladder contraction, gut motility, satiety, and inhibit acid secretion from the stomach. Moreover, they are major neurotransmitters in the brain and the periphery. CCK peptides also stimulate calcitonin, insulin, and glucagon secretion, and they may act as natriuretic peptides in the kidneys. CCK peptides are derived from proCCK with a C-terminal bioactive YMGWMDFamide sequence, in which the Y-residue is partly O-sulfated. The plasma forms are CCK-58, -33, -22, and -8, whereas the small CCK-8 and -5 are potent neurotransmitters. Over the last decades, CCK-expression has also been encountered in tumors (neuroendocrine tumors, cerebral astrocytomas, gliomas, acoustic neuromas, and specific pediatric tumors). Recently, a metastastic islet cell tumor was found to cause a specific CCKoma syndrome, suggesting that circulating CCK may be a useful tumor marker.